2009
DOI: 10.1007/s00256-009-0769-8
|View full text |Cite
|
Sign up to set email alerts
|

The application of T1 and T2 relaxation time and magnetization transfer ratios to the early diagnosis of patellar cartilage osteoarthritis

Abstract: T1 and T2 relaxation times are relatively sensitive to early degenerative changes in the patellar cartilage, whereas the MTR may have some limitations with regard to early detection of OA. In addition, The T1 and T2 relaxation times negatively correlate with each other, which is a novel finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 28 publications
2
44
2
Order By: Relevance
“…This was attributed to the depth-wise variation in cartilage collagen content as well as variations in the radial orientation of collagen fibrils and variations in the bound water fraction throughout the thickness of the cartilage. Yao et al [76] reported on the insensitivity of MTR measurements to early degenerative changes in cartilage, also suggesting that the dependence of the MTR on multiple factors makes variation in MTRs difficult to interpret.…”
Section: Magnetisation Transfermentioning
confidence: 99%
“…This was attributed to the depth-wise variation in cartilage collagen content as well as variations in the radial orientation of collagen fibrils and variations in the bound water fraction throughout the thickness of the cartilage. Yao et al [76] reported on the insensitivity of MTR measurements to early degenerative changes in cartilage, also suggesting that the dependence of the MTR on multiple factors makes variation in MTRs difficult to interpret.…”
Section: Magnetisation Transfermentioning
confidence: 99%
“…Focal increases in T 2 values relative to surrounding cartilage are associated with loss of matrix integrity [81], cartilage lesions [83] and damage to the underlying bone [84]. While focal increases in T 2 are characteristic of degenerated cartilage [85], overall increases in T 2 can occur with normal ageing [46,86]. T 2 patterns also differ between normal cartilage and cartilage with pre-radiographic and radiographic damage [87].…”
Section: T 2 Mappingmentioning
confidence: 99%
“…Some studies have used dGEMRIC to compute GAG content in healthy cartilage [31] and cartilage with preradiographic damage [49]. Overall, T 1,Gd is lower with preradiographic damage [47] and with radiographic cartilage damage and OA [43,46,48] when compared with healthy joints. T 1,Gd also correlates with radiographic scores of OA [43,44], joint alignment [43,45,101] and measures of joint pain [45].…”
Section: T 1 Mapping and Delayed Gadolinium-enhanced Magnetic Resonanmentioning
confidence: 99%
“…Previous studies demonstrated that T2 relaxation times could differentiate OA patients and normal controls, which illustrates the clinical relevance of these measurements [23][24][25]47]. Li et al examined 16 healthy volunteers without clinical or radiological evidence of OA and 10 patients with early OA [24].…”
Section: Association Of T2 Measurements With Oamentioning
confidence: 94%